2009
DOI: 10.1111/j.1745-4530.2007.00229.x
|View full text |Cite
|
Sign up to set email alerts
|

SOME PHYSICOMECHANICAL AND NUTRITIONAL PROPERTIES OF BARBERRY (BERBERIS VULGARIS L.) FRUITS

Abstract: The barberry (Berberis vulgaris L.) fruits growing wild in Turkey were analyzed for some physical (dimensions, geometric mean diameter, sphericity, bulk density, fruit density, volume, terminal velocity, hardness and porosity) and chemical (moisture, reducing sugar, ascorbic acid, total anthocyanin and phenolics, crude protein, crude oil, crude energy, crude fiber, ash, pH, acidity, alcohol‐soluble extract and color) properties. Mineral content of barberry fruits growing wild in Turkey was determined by induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 25 publications
4
34
0
Order By: Relevance
“…The results indicated variations in fruit size and weight among the plants of different locations. Similar results have been reported by Akbulut et al [24]. Environmental factors such as temperature, sunlight, rainfall, snowfall and hail storms vary greatly from zone to zone and locality to locality in the State of Azad Jammu and Kashmir, which ultimately affect fruit size and weight [6].…”
Section: Ahmed Et Alsupporting
confidence: 80%
“…The results indicated variations in fruit size and weight among the plants of different locations. Similar results have been reported by Akbulut et al [24]. Environmental factors such as temperature, sunlight, rainfall, snowfall and hail storms vary greatly from zone to zone and locality to locality in the State of Azad Jammu and Kashmir, which ultimately affect fruit size and weight [6].…”
Section: Ahmed Et Alsupporting
confidence: 80%
“…Regarding fruit traits of B. vulgaris, AKBULUT et al (2009) reported much lower values for the wild population of B. vulgaris growing in Turkey. For example, average fruit length, width and mass are reported to be 7.69 mm, 3.32 mm, and 0.07 g, (compared with the average value range for the same traits in this investigation, that is, 10.20-11.29 mm, 5.29-5.83 mm and 0.1602-0.2199 g).…”
Section: Discussionmentioning
confidence: 91%
“…At the same time, when dealing with the fruit and seed properties of barberry species in relation with interannual variation (HERRERA 1998, ALLEN andWILSON 1992), papers are mainly concentrated on the seed and/or fruit production. Even though data regarding basic fruit and seed related traits for some of the European species of the genus Berberis, namely B. vulgaris (RUDOLF 1974, AKBULUT et al 2009) and B. hispanica (OBESO and HERRERA 1994) could be found, those concerning B. croatica are lacking. B. croatica is a species with a still unresolved taxonomic status and is still not recognized as a distinctive species by the leading authorities on European flora.…”
Section: Introductionmentioning
confidence: 99%
“…These differences in results could be due to the cell structure, and the volume and mass variation characteristics of grains and seeds as moisture content increases (Baryeh 2002). The true and bulk densities of dried Berberis fruits at 27.90% moisture levels are found to be lower than that of fresh barberries (Berberis vulgaris L.) fruits (Akbulut et al 2009). …”
Section: True and Bulk Densitymentioning
confidence: 98%
“…Fruits of Berberis sp. are edible and rich in vitamin C and contain a large amount anthocyanin (Wallace and Giusti 2008;Akbulut et al 2009;Parichehr and Golkho 2009). Anthocyanins and other phenolic compounds are potent scavengers of free radicals, although they can also behave as pro-oxidants (Konczak and Zhang 2004).…”
Section: Introductionmentioning
confidence: 99%